THE CHARACTERISTICS OF ASSESSMENT INSTRUMENT FOR CREATIVE THINKING ABILITY ON CRUDE OIL TOPIC - Monika, Nanda Resti (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
The development of globalization era also has an impact on the change in the world of education. The education which is demanded in the learning process is 21st-century learning. One of the important aspects of 21st century learning is requiring the students to have the ability to think creatively. Creative thinking ability of the students in the learning process is not apart from the teachers' role. The description of students' creative thinking ability is measured by conducting an assessment. This research aims to know the characteristics of assessment instruments for creative thinking on crude oil topic (construct validity, reliability, the level of difficulty, and question differentiation). This research used Research and Development (R&D) method which referred to Borg and Gall model. The technique of selecting the samples was Purposive Random Sampling. The research samples were 80 students of Grade XII Senior High School in Pekanbaru City. The technique of data analysis used SPSS Program 24.0. The results of the validity construct for each question is > 0,208 with 18 questions are stated valid, the reliability test is 0,846. The percentage level of difficulty obtained 22,222% questions are categorized into easy, 61,111% questions are medium, and 16,667% questions are categorized into difficult. The percentage of question differentiation obtained 16,667% questions are good, 66,667% is fair, and 11,111% is bad.